An uncertainty approach to modelling climate change risk in South Africa - James Cullis; Theresa Alton; Channing Arndt; Anton Cartwright; Alice Chang; Sherwin Gabriel; Yohannes Gebretsadik; Faaiqa Hartley; Gerald de Jager; Konstantin Makrelov; Gordon Robertson; C. Adam Schlosser; et al. (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study represents the first attempt at an integrated approach to assessing the potential impacts of climate change on the national economy of South Africa via a number of (but not necessarily all) impact channels. The study focuses on outcomes by about 2050. The results show the multiple impacts of climate change and the importance of spatial and temporal variation in these impacts. The study focused in particular on the potential impacts of climate change on the water supply sector, dry-land agriculture, hydropower, roads infrastructure costs and sea level rise. These factors have not been previously considered in a fully integrated way for South Africa. The study considers two future global emissions scenarios - an Unconstrained Emission Scenario (UCE) where global policies to reduce emissions fail to materialize and a Level 1 Stabilization Scenario (L1S) where aggressive emissions policies are pursued. Based on the full range of impact channels considered, economic impacts are showed to be potentially significant particularly resulting from additional roads infrastructure costs and variability in dryland agricultural yields, with only limited impacts due to variability in the ability to supply future water demands. The total impact of climate change on the level of real GDP by about 2050 is found to range between -3.8% and 0.3% compared with a fictional 'no climate change' baseline. While positive outcomes are possible, results indicate that, for the very large majority of climate futures, the impact on total GDP will be negative. The median result shows that by 2050, South Africa's real GDP level will be about 1.5% lower than in the baseline scenario. This translates into a 0.03 percentage point decline in average annual real GDP growth rate. The net present value of the potential impact on GDP out to 2050 is highly variable, ranging from losses of R 930 billion to gains of R 310 billion (real 2007 Rand). About 96% of the climates scenarios show overall losses. The median loss in NPV is approximately Rand 259 billion which, at more than 10% of 2007 GDP, is sizeable and should motivate for action in terms of both mitigation and consideration and funding of potential adaptation scenarios.
Keywords: O5; O2; Q54; Q56; 330; climate change; South Africa; runoff; streamflow; uncertainty; water resources; crop yields; roads; sea-level rise; impacts; adaptation; economic growth; development